2009
DOI: 10.1186/1472-6963-9-4
|View full text |Cite
|
Sign up to set email alerts
|

What promotes sustainability in Safe Community programmes?

Abstract: Background: The theory and practice of safety promotion has traditionally focused on the safety of individuals. This study also includes systems, environments, and organizations. Safety promotion programmes are designed to support community health initiatives taking a bottom-up approach. This is a long-term and complex process. The aim of this study was to try to empirically identify factors that promote sustainability in the structures of programmes that are managed and coordinated by the local government.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Meanwhile, it has been largely argued that safety and crime are particularly linked to sustainability (Armitage & Gamman, 2009;Cozens, 2002;Dewberry, 2003;Du Plessis, 1999) and place attachment (Kamalipour, Yeganeh, & Alalhesabi, 2012;Scannell & Gifford, 2010). In this way, crime prevention focuses on the efforts contributing to the aim of decreasing crime and fear of crime (Marzbali et al, 2012b;Nordqvist, Timpka, & Lindqvist, 2009) in order to minimize possible problems of new designs based on previous practices (Clarke, 2009). In this way, crime prevention through environmental design (CPTED) denotes that an effective usage of built environment along with proper design interventions could improve the quality of life and decrease fear of crime (FOC) and crime occurrence (Crowe, 2000).…”
Section: Urban Crime: Crime Prevention Through Environmental Design Amentioning
confidence: 99%
“…Meanwhile, it has been largely argued that safety and crime are particularly linked to sustainability (Armitage & Gamman, 2009;Cozens, 2002;Dewberry, 2003;Du Plessis, 1999) and place attachment (Kamalipour, Yeganeh, & Alalhesabi, 2012;Scannell & Gifford, 2010). In this way, crime prevention focuses on the efforts contributing to the aim of decreasing crime and fear of crime (Marzbali et al, 2012b;Nordqvist, Timpka, & Lindqvist, 2009) in order to minimize possible problems of new designs based on previous practices (Clarke, 2009). In this way, crime prevention through environmental design (CPTED) denotes that an effective usage of built environment along with proper design interventions could improve the quality of life and decrease fear of crime (FOC) and crime occurrence (Crowe, 2000).…”
Section: Urban Crime: Crime Prevention Through Environmental Design Amentioning
confidence: 99%
“…The Safe Community research group at Linko¨ping University, led by Professors T. Timpka and K. Lindqvist (Nordqvist, Timpka, & Lindqvist, 1999), has raised some very important evaluation issues, based on analyses of Safe Community programmes, a longterm and complex process. In a focus group study, they found collaboration and personal contacts to be the basis for sustainability.…”
Section: Discussionmentioning
confidence: 99%
“…The collaboration factor is one of the main differences between the medical focus and comprehensive CBR. To ensure sustainability, cross-disciplinary collaboration is essential (Gruen et al, 2008;Nordqvist et al, 2009). If collaboration is good within a comprehensive programme, there is greater likelihood that the programme will be more sustainable than the purely medical focus, because of a bigger network of all kinds of resources.…”
Section: Discussionmentioning
confidence: 99%